TD-LTE refinement planning and marketing based on user behavior - Congsheng QI; Guibin TIAN (Dianxin kexue)
The planning and marketing situation of TD-LTE were analyzed,the analysis to the user terminal usage and user service was carried on,the influence of distribution of users and user terminal types of data traffic were analyzed,the process of TD-LTE in meticulous planning and marketing according to the user behavior were determined,the process through the TD-LTE fine planning and marketing practical application were verified.